Comparative characteristic of the brain natriuretic peptide and angiotensin II expression index in the structure of locus coeruleus of brain stem in rats with arterial hypertension of various origins - Danukalo, M. V.; Hancheva, O. V.; Kadzharian, Ye. V.; Данукало, Максим Вікторович; Ганчева, Ольга Вікторівна; Каджарян, Єлизавета Віталіївна (Запорізький державний медичний університет, 2019)
The aim of our study was to determine the characteristics of the BNP and AT II expression in the LC structure of rat brain stem with experimental (genetically determined essential and secondary endocrine-salt) arterial hypertension and to give a comparative description of the expression pattern of these peptides in etiologically different types of arterial hypertension. Materials and methods. The study was carried out on adult 30 male rats. 20 Wistar animals were divided into two groups – control (10 rats) and 10 rats with simulated endocrine-salt AH (ESAH) and 10 rats of SHR line with essential AH (EAH). The expression parameters of neuropeptides, such as the content, concentration, and relative area of the immunoreactive material, were studied using an immunohistochemical method. Results. It was found that from all BNP expression parameters in the locus coeruleus structure, only relative area increased significantly in both groups. The concentration did not significantly change, and the content of immunoreactive material increased significantly only in animals with ESAH. At the same time, all parameters of angiotensin II expression increased significantly in both experimental groups. Thus, in rats with experimental arterial hypertension in the locus coeruleus structure, more pronounced changes in expression parameters are characteristic for angiotensin II, rather than for BNP. There is a discrepancy between levels of pressor angiotensin II expression and depressor BNP expression in the direction of angiotensin II expression increasing during the arterial hypertension formation. The nature and peculiarities of these neuropeptides expression in the LC structure depend on the key link of the pathogenesis of the modeled arterial hypertension. Conclusions. In rats of the control group with normal blood pressure in LC structure, AT II is more represented. The content and concentration of IRM to AT II are 2.32 and 2.19 times higher than the corresponding BNP values. Prevalence of AT II in the LC structure of the brainstem remains even when arterial hypertension is formed, regardless of its etiology. However, the etiopathogenetic mechanisms of arterial hypertension development impose their own characteristics. In EAH, the content and concentration of AT II is higher than BNP by 4.58 and 3.59 times; in ESAH – by 2.16 and 2.83 times. In the pathogenesis of essential arterial hypertension formation an important role is played by a change in the central control of blood pressure regulation. It is characterized by a significant predominance of the pressor component AT II over the depressor BNP in the brainstem LC structure.Мета роботи – встановити особливості показників експресії мозкового натрійуретичного пептиду (BNP) та ангіотензину ІІ (АТ ІІ) у структурі блакитної плями (БП) стовбура мозку щурів з експериментальними (генетично детермінованою есенціальною та вторинною ендокринно-сольовою) артеріальними гіпертензіями (АГ), дати порівняльну характеристику паттерна експресії цих пептидів при етіологічно різних видах артеріальної гіпертензії. Матеріали та методи. Дослідження виконали на 30 статевозрілих щурах-самцях, серед них – 20 тварин лінії Wistar, яких поділили на дві групи: 10 – контроль, 10 – зі змодельованою ендокринно-сольовою АГ (ЕСАГ); 10 щурів лінії SHR з есенціальною АГ (ЕАГ). Параметри експресії нейропептидів: вміст, концентрацію та відносну площу імунореактивного матеріалу – досліджували за допомогою імуногістохімічного методу. Результати. Встановили, що серед досліджуваних параметрів експресії BNP у структурі БП вірогідно в обох групах збільшилась тільки відносна площа; концентрація вірогідно не змінилася, а вміст імунореактивного матеріалу вірогідно виріс тільки у тварин з ЕСАГ. Водночас усі показники експресії ангіотензину II вірогідно збільшилися в обох експе-риментальних групах. Отже, в щурів з експериментальною артеріальною гіпертензією у структурі блакитної плями вираженіші зміни показників експресії були характерні для ангіотензину ІІ, ніж для BNP. Так, при сформованій артеріальній гіпертензії спостерігали невідповідність між рівнями експресії пресорного ангіотензину ІІ і депресорного BNP у бік збільшення експресії ангіотензину ІІ. Характер та особливості експресії досліджуваних нейропептидів у структурі блакитної плями залежать від ключової ланки патогенезу змодельованої артеріальної гіпертензії. Висновки. У щурів контрольної групи з нормальним артеріальним тиском у структурі блакитної плями значушо представленим є АТ ІІ, вміст і концентрація якого у 2,32 та 2,19 раза перевищує відповідні показники BNP. При сформованій артеріальній гіпертензії, незалежно від її етіології, переважання АТ ІІ у структурі блакитної плями стовбура мозку зберігається. Але патогенетичні механізми розвитку артеріальної гіпертензії зумовлюють свої особливості. Під час ЕАГ підвищення вмісту й концентрації АТ ІІ порівняно з BNP становить 4,58 і 3,59 раза; при ЕСАГ – у 2,16 і 2,83 раза. У патогенезі формування есенціальної артеріальної гіпертензії важливу роль відіграють зміни центрального контура регуляції артеріального тиску, характерне суттєве переважання пресорного компонента АТ ІІ у структурі блакитної плями стовбура мозку над депресорним BNP. Цель работы – установить особенности показателей экспрессии мозгового натрийуретического пептида (BNP) и ангиотензина ІІ (АТ II) в структуре голубого пятна (ГП) ствола мозга крыс с экспериментальными (генетически детерминированной эссенциальной и вторичной эндокринно-солевой) артериальными гипертензиями (АГ), дать сравнительную характеристику паттерна экспрессии этих пептидов при этиологически разных видах артериальной гипертензии. Материалы и методы. Исследование проведено на половозрелых 30 крысах-самцах, среди которых 20 животных линии Wistar, поделенных на 2 группы: 10 – контроль, 10 – со смоделированной эндокринно-солевой АГ (ЭСАГ); 10 крыс линии SHR с эссенциальной АГ (ЭАГ). Параметры экспрессии нейропептидов: содержание, концентрацию и относительную площадь иммунореактивного материала – исследовали с помощью иммуногистохимического метода. Результаты. Установлено, что из исследуемых параметров экспрессии BNP в структуре голубого пятна достоверно в обеих группах увеличилась лишь площадь; концентрация достоверно не изменилась, а содержание иммунореактивного материала достоверно возросло лишь у животных с ЭСАГ. Все показатели экспрессии ангиотензина ІІ достоверно выросли в обоих экспериментальных группах. Таким образом, у крыс с экспериментальной артериальной гипертензией в структуре голубого пятна более выраженные изменения показателей экспрессии характерны для ангиотензина ІІ, чем для BNP. Так, при сформированной артериальной гипертензии отмечено несоответствие между уровнями экспрессии прессорного ангиотензина ІІ и депрессорного BNP в сторону увеличения экспрессии ангиотензина ІІ. Характер и особенности экспрессии изучаемых нейропептидов в структуре голубого пятна зависят от ключевого звена патогенеза моделированной артериальной гипертензии. Выводы. У крыс контрольной группы с нормальным артериальным давлением в структуре голубого пятна более представленным является АТ II, содержание и концентрация которого в 2,32 и 2,19 раза превышают соответствующие показатели BNP. При сформированной артериальной гипертензии, независимо от ее этиологии, преобладание АТ II в структуре голубого пятна ствола мозга сохраняется. Однако этиопатогенетические механизмы развития АГ накладывают свои особенности. При ЭАГ превышение содержания и концентрации АТ II по сравнению с BNP составляет 4,58 и 3,59 раза; при ЭСАГ – в 2,16 и 2,83 раза. В патогенезе формирования эссенциальной артериальной гипертензии важную роль играет изменение центрального контура регуляции артериального давления, характерно существенное преобладание прессорного компонента АТ II в структуре голубого пятна ствола мозга над депрессорным BNP.
Порівняльна характеристика показників експресії мозкового натрійуретичного пептиду та ангіотензину ІІ у структурі блакитної плями стовбура мозку щурів при артеріальній гіпертензії різного ґенезу
Сравнительная характеристика паттерна экспрессии мозгового натрийуретического пептида и ангиотензина II в структуре голубого пятна ствола мозга крыс при артериальной гипертензии различного генеза
Keywords: brain natriuretic peptide; angiotensin II; locus coeruleus; brain stem; arterial hypertension; rats; мозковий натрійуретичний пептид; ангіотензин II; locus coeruleus; стовбур мозку; артеріальна гіпертензія; щури; мозговой натрийуретический пептид; ангиотензин II; ствол мозга; артериальная гипертензия; крысы